2022
DOI: 10.1042/bsr20211812
|View full text |Cite
|
Sign up to set email alerts
|

The paradigm of drug resistance in cancer: an epigenetic perspective

Abstract: Innate and acquired resistance towards the conventional therapeutic regimen imposes a significant challenge for the successful management of cancer for decades. In patients with advanced carcinomas, acquisition of drug resistance often leads to tumor recurrence and poor prognosis after the first therapeutic cycle. In this context, cancer stem cells (CSCs) are considered as the prime drivers of therapy resistance in cancer due to their ‘non-targetable’ nature. Drug resistance in cancer is immensely influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 313 publications
(220 reference statements)
0
21
0
Order By: Relevance
“…For decades, drug resistance towards the conventional therapeutic regimens has imposed a significant challenge for the successful management of cancer. Epigenetic modifications play a crucial role in the individual patient’s response to anticancer drugs and in drug resistance [ 146 ]. Based on the data presented here, Top I inhibitors are one of the major anticancer families affected by epigenetic alterations.…”
Section: Expert Opinionmentioning
confidence: 99%
“…For decades, drug resistance towards the conventional therapeutic regimens has imposed a significant challenge for the successful management of cancer. Epigenetic modifications play a crucial role in the individual patient’s response to anticancer drugs and in drug resistance [ 146 ]. Based on the data presented here, Top I inhibitors are one of the major anticancer families affected by epigenetic alterations.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Excessive drug efflux is considered a critical mechanism contributing to cancer drug resistance, in which the efficiency of anticancer drugs is significantly limited due to the reduction in drug concentration in cancer cells ( 150 ). It has been reported that excessive drug efflux is a result of the upregulation of drug efflux pumps, including ATP-binding cassette (ABC) transporters.…”
Section: Mechanisms Of Ncrnas In Mediating Cancer Drug Resistancementioning
confidence: 99%
“…Cancer is a highly prevalent and lethal global disease, second only to cardiovascular disease in terms of its impact 9 . Gastric cancer (GC) is a widespread malignancy, accounting for around 1,090,000 new instances and 770,000 fatalities in 2020 globally.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a highly prevalent and lethal global disease, second only to cardiovascular disease in terms of its impact. 9 Gastric cancer (GC) is a widespread malignancy, accounting for around 1,090,000 new instances and 770,000 fatalities in 2020 globally. Based on these statistics, GC ranks as the fifth most prevalent cancer and is the fourth most common cause of cancer-related mortality.…”
Section: Introductionmentioning
confidence: 99%